2021
DOI: 10.1186/s12263-021-00684-6
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between dietary branched-chain amino acids and genetic risk score on the risk of type 2 diabetes in Chinese

Abstract: Background and objectives Previous studies have found the important gene-diet interactions on type 2 diabetes (T2D) incident but have not followed branched-chain amino acids (BCAAs), even though they have shown heterogeneous effectiveness in diabetes-related factors. So in this study, we aim to investigate whether dietary BCAAs interact with the genetic predisposition in relation to T2D risk and fasting glucose in Chinese adults. Methods In a case-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…While histidine may have some beneficial health effects (i.e., antioxidant activity), histidine metabolites and related imidazole derivatives may be associated with impaired insulin signaling, type 2 diabetes, and kidney disease [ 53 , 54 ]. Several cross-sectional studies have shown positive associations of branched chain amino acids with cardiovascular disease risk, metabolic dysregulation, impaired glucose signaling and insulin resistance [ 55 , 56 , 57 ], and a number of studies have shown positive associations with type 2 diabetes [ 58 , 59 , 60 ]. Ceramides are critical lipid signaling molecules, and have various and complex biological roles.…”
Section: Discussionmentioning
confidence: 99%
“…While histidine may have some beneficial health effects (i.e., antioxidant activity), histidine metabolites and related imidazole derivatives may be associated with impaired insulin signaling, type 2 diabetes, and kidney disease [ 53 , 54 ]. Several cross-sectional studies have shown positive associations of branched chain amino acids with cardiovascular disease risk, metabolic dysregulation, impaired glucose signaling and insulin resistance [ 55 , 56 , 57 ], and a number of studies have shown positive associations with type 2 diabetes [ 58 , 59 , 60 ]. Ceramides are critical lipid signaling molecules, and have various and complex biological roles.…”
Section: Discussionmentioning
confidence: 99%
“…Since high BCAA intake has been associated with increased incident T2D risk in earlier studies and our previous study [ 22 ], we analyzed the effect of BCAA intakes on the risk of type 2 diabetes among different GRS. Significant GRS-BCAA intakes interactions in relation to T2D risk were observed after multivariate adjustment(total BCAAs: P for interaction = 0.023; Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Both the genetic variant and the gut bacteria are associated with altered circulating levels of BCAAs 28,29 . Several prospective cohort studies have identi ed BCAAs as a predictor of Type 2 Diabetes (T2D) risk which is in uenced by genetic predisposition [30][31][32][33][34] . In our study, bacteria associated with host genomic non-coding regions were associated with host defense to pathogen invasion, including membrane integrity, innate immune defense and antibacterial mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic predisposition and the gut microbiome may interact to increase systemic levels of BCAA, essential amino acids from diet and the microbiome that predict risk of T2D 28, [30][31][32][33][34]59 . In our study, Prevotella-9 was positively associated with a SNP in the BCAA transferase gene (rs10743525; BCAT1).…”
Section: Discussionmentioning
confidence: 99%